ANALISIS OPTIMALISASI PENGUKURAN GNSS STATIK MENGGUNAKAN JARING RADIAL - Ariyantoni, Johan; Ahmad Ridho Sastra; Annisa Mustika (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
ABSTRACT Determining a position has progressed quite rapidly, this progress is of course closely related to the increasing development of satellite-based positioning technology, one of which is the Global Navigation Satellite System (GNSS). The GNSS system has developed along with advances in science and technology so that it can now capture signals from GPS, Galileo, Beidou and Glonass satellites. GNSS surveys have several methods, namely rapid static, stop and go, real time, and pseudo kinematic. One method that is often used is the Static method, there are many activities that require the implementation of static GNSS observations, one of which is for measuring Ground Control Points (GCP). In this research, measurements were carried out in Gunung Sitoli City, North Sumatra using a static method with radial net mode to determine the comparison between 2 different schemes, namely the 15 point and 20 point GCP schemes. The data processing process for this research was carried out using Eoffice software, which is special software that can only be used to process data from Efix Geodetic GPS. Accuracy analysis was carried out using Fisher's test and based on horizontal vertical accuracy. Based on the results of the Fisher test, it shows that there is no significant difference between schemes A & B. Meanwhile, analysis based on the horizontal vertical accuracy of the 15 GCP point A scheme has better horizontal accuracy and vertical accuracy than the 20 GCP point B scheme with an average horizontal accuracy of 0. 00566 and Vertical 0.0074 in scheme A and horizontal accuracy 0.00772 and vertical 0.00697 from scheme B. Determining the location of points and the distribution of points affects the accuracy of the results, both schemes have DOP values with an average of HDOP 1.3, VDOP 0.6 and PDOP 1.1 which are included in ideal criteria. Keywords: GNSS, Static Method, GCP ABSTRAK Padapenelitian ini pengukuran dilakukan di Kota Gunung Sitoli Sumatera Utara menggunakan metode statik dengan moda jaring radial untuk mengetahui perbandingan antara 2 skema berbeda yakni skema 15 titik dan 20 titik GCP. Proses pengolahan data penelitian ini dilakukan dengan menggunakan software Eoffice yang merupakan software khusus yang hanya bisa digunakan untuk proses pengolahan data dari GPS Geodetik Efix. Analisis ketelitian dilakukan dengan uji fisher dan berdasarkan akurasi horizontal vertikal. Hasil uji fisher menunjukkan tidak ada perbedaan yang signifikan antara skema A dan B sedangkan, analisis berdasarkan akurasi horizontal vertikal skema A 15 titik GCP memiliki ketelitian horizontal dan ketelitian vertikal yang lebih baik dibanding skema B 20 titik GCP, dengan rata-rata ketelitian Horizontal 0,00566 dan Vertikal 0,0074 pada skema A dan ketelitian horizontal 0,00772 dan vertikal 0,00697 dari skema B. Penentuan lokasi titik dan persebaran titik sangat berpengaruh terhadap hasil ketelitian, kedua skema memiliki nilai DOP dengan rata-rata HDOP 1,3, VDOP 0,6 dan PDOP 1,1 yang masuk dalam kriteria ideals. Kata Kunci : GNSS, Metode Statik, GCP